Institutional logics in the field of transnational higher education - Ammann, Matthias (online, 2017)
The post-industrialized world has reached the vanguard of the knowledge based society. There the creation of knowledge and delivering of education have become a pivotal asset. In the era of worldwide integration of goods, services, and people, higher education organizations today heavily depend upon the international interaction of individuals and the exchange of information. Higher education organizations always maintained international relations, globalization, however, increased the size, scope and intensity in an unprecedented way. These developments introduced a new paradigm of competition for resources in the field of higher education. It causes additional demands and expectations vis-à-vis higher education organizations which they have to address in one way or the other. This research project investigates one of the consequences, the phenomenon of a rising number of offshore organizations of universities. Literature of this field studies either globalization of higher education as a general topic and herewith examines policies and national strategies or it studies cases of offshore organizations stressing the cultural normative aspect. Therefore, this work introduced institutional theory to combine the macro with the micro perspective which generates reliable explanations for raised questions in that field. The thesis discusses the topic along three main questions: (1) What are the underlying institutional logics which shape the field of transnational higher education? (2) When does institutional complexity become evident and how are offshore organizations of universities responding to institutional complexity? (3) How can responses of offshore organizations be managed in a way that supports a favorable outcome of the operations? Collected data originate from a two year field research between 2013 and 2015. The study analyzes 25 offshore organizations of universities located in Singapore and surroundings with their parent organizations originally based in Australia, United Kingdom, Germany, Ireland, New Zealand, Switzerland, and the United States of America. In total 40 semi-structured interviews were carried out with members of offshore organizations who have managerial responsibilities, which resulted in 42 hours of recorded audio material. Approximately 600 pages of transcribed interview tapes were analyzed to identify practices, assumptions, values, beliefs and rules. The analysis shows that there are six competing institutional logics which cause institutional complexity. Not only do they struggle for dominance they are also in conflict with each other. This means that following one script of appropriate behavior leads to denial of another one. Thus responses to these various demands and expectations are manifold. However, there are three organizational attributes which define the way how organizations are addressing institutional complexity. The manipulation of these three features allows the management to control the way how offshore organizations response to competing demands and expectations. As a result offshore organizations are able to align the response with the strategic intent of the operation. Die post-industrialisierte Welt hat ihren Höhepunkt in der wissensbasierten Gesellschaft erreicht. In dieser sind Wissen und Bildung ein zentrales Gut geworden. Im Zeitalter der weltweiten Verflechtung von Waren, Dienstleistungen und Gesellschaften sind Universitäten stark von den transnationalen Beziehungen zwischen Individuen und dem grenzüberschreitenden Austausch von Informationen abhängig. Universitäten waren immer schon international vernetzt, jedoch verstärkte die Globalisierung Qualität, Ausmass und Intensität dieser Abhängigkeiten in einer noch nie da gewesenen Weise. Diese Entwicklung führen einerseits zu mehr Wettbewerb um Ressourcen, andererseits zu steigenden Forderungen und Erwartungen gegenüber den Hochschuleinrichtungen. Die vorliegende Forschungsarbeit untersucht eine dieser Konsequenzen: das Phänomen der aufkommenden Offshore Organisationen von Universitäten. Bis anhin haben sich Studien in diesem Bereich entweder auf die makroökonomischen Trends bezogen, indem sie Bildungspolitik von Ländern untersuchen oder auf einzelne Fallstudien fokussiert, welche kulturelle Faktoren beleuchten. Diese Arbeit verwendet die Theorie des Institutionalismus, welche die Makro- und Mikroperspektive vereint und damit zuverlässige Erklärungen für die in diesem Gebiet aufgeworfenen Fragen bereitstellt. Die Diskussion wird anhand dreier Hauptfragen geführt: (1) Was sind die zugrunde liegenden institutionellen Logiken, die das Feld der transnationalen Bildung formen? (2) Inwiefern geraten diese sich konkurrierenden institutionellen Logiken in Konflikte und wie reagieren Offshore Organisationen auf diese institutionelle Komplexität? (3) Wie können Reaktionen der Offshore Organisationen auf institutionelle Komplexität gesteuert werden, um ein erfolgreiches Wirtschaften der Organisation sicherzustellen? Die gesammelten Daten entstammen einer zweijährigen Feldforschung zwischen 2013 bis 2015. Die Arbeit analysiert 25 in Singapur und unmittelbarer Nähe ansässige Offshore Organisationen von Universitäten, deren Stammuniversitäten sich in Australien, Grossbritannien, Deutschland, Irland, Neuseeland, Schweiz und den USA befinden. Gesamthaft wurden 40 halb-strukturierte Interviews mit Mitgliedern in Managementfunktionen dieser Offshore Organisationen geführt. Diese wurden in 42 Stunden Audiomaterial festgehalten. Ungefähr 600 Standartseiten transkribierter Interviewaufnahmen wurden analysiert, um Praktiken, Werte, Überzeugungen und Richtlinien verschiedenen Feld-Logiken zuzuweisen. Die Analyse zeigt sechs konkurrierende institutionelle Logiken auf, die institutionelle Komplexität auslösen. Sie ringen nicht nur um Dominanz, sondern stehen in gegenseitigem Konflikt. Dies bedeutet, dass das Befolgen einer handlungsanleitenden Richtlinie die Verwendung einer anderen institutionellen Logik ausschliesst. Daher sind Reaktionen auf die Vielzahl von Forderungen und Erwartungen unterschiedlich ausgestaltet. Allerdings wird in dieser Arbeit angenommen, dass es drei organisationale Attribute gibt, welche Art und Weise bestimmen, wie Organisationen institutionelle Komplexität adressieren. Das Management kann durch Einflussnahme auf diese drei Attribute die Reaktion auf konkurrierende Anforderungen und Erwartungen steuern. Offshore Organisationen sind somit in der Lage Reaktionen gegenüber institutioneller Komplexität auf das eigentliche Ziel der Unternehmung optimal anzupassen.
Dissertation no. 4577
Keywords: Graue Literatur; Hochschulschrift; Aufsatzsammlung; Universität; Offshoring; Zweigniederlassung; Institutionalismus; Singapur; Higher Education; Transnational Higher Education; International Branch Campus; Institutional Theory; Institutional Logics; Geschichte 2013-2015